Jnk1 in murine hepatic stellate cells is a crucial mediator of liver fibrogenesis. Issue 7 (13th September 2013) - Zhao, Gang; Hatting, Maximilian; Nevzorova, Yulia A.; Peng, Jin; Hu, Wei; Boekschoten, Mark V; Roskams, Tania; Muller, Michael; Gassler, Nikolaus; Liedtke, Christian; Davis, Roger J; Cubero, Francisco Javier; et al.
Abstract : Objective: The c-Jun N-terminal kinase-1 (Jnk1) gene has been shown to be involved in liver fibrosis. Here, we aimed to investigate the molecular mechanism and define the cell type involved in mediating the Jnk1-dependent effect on liver fibrogenesis. Design: Jnk1 f/f wildtype (WT), Jnk1 −/− and Jnk1 Δhepa (hepatocyte-specific deletion of Jnk1) mice were subjected to (i) bile duct ligation (BDL) and (ii) CCl4 -induced liver fibrosis. Additionally, we performed bone marrow transplantations (BMT), isolated primary hepatic stellate cells (HSCs), studied their activation in vitro and investigated human diseased liver samples. Results: Phosphorylated Jnk was expressed in myofibroblasts, epithelial and inflammatory cells during the progression of fibrogenesis in humans and mice. In mice, liver transaminases, alkaline phosphatase, bilirubin and liver histology revealed reduced injury in Jnk1 −/− compared with WT and Jnk1 Δhepa mice correlating with lower hepatocyte cell death and proliferation. Consequently, parameters of liver fibrosis such as Sirius red staining and collagen IA1 and α-smooth muscle actin expression were downregulated in Jnk1 −/− compared with WT and Jnk1 Δhepa livers, 4 weeks after CCl4 or BDL. BMT experiments excluded bone marrow–derived cells from having a major impact on the Jnk1-dependent effect on fibrogenesis, while primary HSCs from Jnk1 −/− livers showed reduced transdifferentiation and extracellular matrix production. Moreover, Jnk1 ablation caused a reduced lifespan and poor differentiation of HSCs into matrix-producing myofibroblasts. Conclusions: Jnk1 in HSCs, but not in hepatocytes, significantly contribute to liver fibrosis development, identifying Jnk1 in HSCs as a profibrotic kinase and a promising cell-directed target for liver fibrosis.